Melatonin directly binds and inhibits death‐associated protein kinase 1 function in Alzheimer’s disease - Chen, Dongmei; Mei, Yingxue; Kim, Nami; Lan, Guihua; Gan, Chen‐Ling; Fan, Fei; Zhang, Tao; Xia, Yongfang; Wang, Long; Lin, Chun; Ke, Fang; Zhou, Xiao Zhen; et al. (Journal of pineal research, 2020)
Death‐associated protein kinase 1 (DAPK1) is upregulated in the brains of human Alzheimer's disease (AD) patients compared with normal subjects, and aberrant DAPK1 regulation is implicated in the development of AD. However, little is known about whether and how DAPK1 function is regulated in AD. Here, we identified melatonin as a critical regulator of DAPK1 levels and function. Melatonin significantly decreases DAPK1 expression in a post‐transcriptional manner in neuronal cell lines and mouse primary cortical neurons. Moreover, melatonin directly binds to DAPK1 and promotes its ubiquitination, resulting in increased DAPK1 protein degradation through a proteasome‐dependent pathway. Furthermore, in tau‐overexpressing mouse brain slices, melatonin treatment and the inhibition of DAPK1 kinase activity synergistically decrease tau phosphorylation at multiple sites related to AD. In addition, melatonin and DAPK1 inhibitor dramatically accelerate neurite outgrowth and increase the assembly of microtubules. Mechanistically, melatonin‐mediated DAPK1 degradation increases the activity of Pin1, a prolyl isomerase known to play a protective role against tau hyperphosphorylation and tau‐related pathologies. Finally, elevated DAPK1 expression shows a strong correlation with the decrease in melatonin levels in human AD brains. Combined, these results suggest that DAPK1 regulation by melatonin is a novel mechanism that controls tau phosphorylation and function and offers new therapeutic options for treating human AD.